(untitled) (Revista Direito em Debate, 2023)
This article studies the possibility of using collective redress mechanisms to remove barriers imposed on the visually impaired. To that end, it analyzes conceptually the terms “person with disability” and “visual impairment”, as well as the so-called “barriers”, considering their existence and the need for their removal as an essential element for the inclusion of this group. It also analyzes the appropriateness and characteristics of collective remedy, concluding for the suitability of its use in this case. This is because the article stresses that the removal of barriers imposed on this group reveals an interest that goes beyond the individual, leading to the most effective use of collective protection. The intention is, considering the provisions of the LBI (Brazilian law), to demonstrate how to effectively guarantee accessibility when considering the procedural approach. The research adopted the methodology of legal-dogmatic research, through bibliographical research.